The Rise of Progressive Cities East and West - Douglass, Mike.; Garbaye, Romain; Ho, K. C.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book explores the leading role that cities can play in shaping progressive policies in collaboration with various stakeholders. It examines the timing of such shifts to progressivity in cities, the interactions that enable progressive actions to be developed and sustained, and the challenges and constraints facing progressive cities. The book approaches the themes using an array of methods to investigate how progressive city governments emerge, what constitutes a "progressive city" in terms of governance institutions, processes and outcomes, and whether progressive cities are destined to be ephemeral or if they can be sustained over time. With its focus on the emerging role of local governments in shaping city futures, this book is useful for students, academics, government officials and policymakers interested in geography, sociology, urban planning, public policy, political economy, social movements, participatory democracy and Asian and European studies.
Section 1 Introduction -- 1.The Rise of Progressive Cities East and West -- 2.Progressive Cities for Human and Planetary Flourishing -- Section 2 Progressive Moments and Movements -- 3.Progressive City in the Making? The Seoul Experience -- 4.Toward the Progressive Science: Creative Activism in Marseille and Istanbul -- 5.Cities of Protest and Cities of Progress -- Section 3 Constructing Progressive Cities from Collaborative Partnerships -- 6.Constructing Progressiveness: The Complexity of Progressive Cities in Surakarta and Surabaya -- 7.Governance with a Creative Citizenry: Public Art Projects for Cultural Vitality in Japanese Cities -- 8.Participative Budgeting and Progressive cities: are London and Paris listening to their own voices? -- 9.Towards a Progressive Chengdu: Land Reform, Participatory Budgeting and Rescaling state-civil relations -- Section 4 Urban Challenges and the Impediments to Sustaining Progressive Agendas -- 10.Migration and inclusion in the European city: the cautionary tale of British cities -- 11.Progressive solutions to urban woes?: Arts and culture as a tool for urban regeneration in Busan, South Korea -- 12.Tackling In-Work Poverty: How Progressive is the London Living Wage? -- 13.Towards a Metropolitan Social Revolution? The Promises and Pitfalls of US Labor Ordinances -- 14.Housing policies in London: policies for a progressive world city?.
Keywords: Sociology, Urban; Culture; Political science; Population -- Economic aspects; Emigration and immigration; Urban Sociology; Sociology of Culture; Governance and Government; Population Economics; Human Migration